Public Administration "Changing Paradigms of Public Administration in Facing the Global Health Crisis: Lessons from the Pandemic" - Hastuti, Puji; Fadhilah, Nurul; Anggraini, Sahwa Desma; Muskin, Isra (Socious Journal, 2024)
The COVID-19 pandemic has changed the paradigm of public administration in dealing with the global health crisis by emphasizing the importance of multilateralism and cross-border cooperation. The government now plays the role of a facilitator that integrates health and political policies to respond more effectively. The study identifies countries with swift and transparent leadership, such as Vietnam, that are better able to respond to the pandemic, while also exposing global inequalities in low-income countries that need international support. Public administration has a crucial role in designing effective policies, providing resources, and implementing measures such as social distancing, with transparent communication to build public trust. The digitization of public services and evidence-based collaboration between governments and scientists have become important pillars in responding to people's needs. This study uses a descriptive-qualitative approach with case studies and comparative analysis of policies in various countries. The results show that adaptation and innovation in public administration, including increasing digital literacy and community participation, are critical to building health system resilience to future crises. This research is expected to contribute to public administration theory and relevant policy recommendations to face similar challenges in the future.